Perceptions of Using Multiple Mobile Health Devices to Support Self‐Management Among Adults With Type 2 Diabetes: A Qualitative Descriptive Study. Issue 5 (29th April 2021) - Lewinski, Allison A.; Vaughn, Jacqueline; Diane, Anna; Barnes, Angel; Crowley, Matthew J.; Steinberg, Dori; Stevenson, Janee; Yang, Qing; Vorderstrasse, Allison A.; Hatch, Daniel; Jiang, Meilin; Shaw, Ryan J.
Abstract: Purpose: This study identified facilitators and barriers pertaining to the use of multiple mobile health (mHealth) devices (Fitbit Alta® fitness tracker, iHealth® glucometer, BodyTrace® scale) that support self‐management behaviors in individuals with type 2 diabetes mellitus (T2DM). Design: This qualitative descriptive study presents study participants' perceptions of using multiple mobile devices to support T2DM self‐management. Additionally, this study assessed whether participants found visualizations, generated from each participant's health data as obtained from the three separate devices, useful and easy to interpret. Methods: Semistructured interviews were completed with a convenience sample of participants (n = 20) from a larger randomized control trial on T2DM self‐management. Interview questions focused on participants' use of three devices to support T2DM self‐management. A study team member created data visualizations of each interview participant's health data using RStudio. Results: We identified two themes from descriptions of study participants: feasibility and usability. We identified one theme about visualizations created from data obtained from the mobile devices. Despite some challenges, individuals with T2DM found it feasible to use multiple mobile devices to facilitate engagement in T2DM self‐management behaviors. Discussion: As mHealth devices become increasingly popular for diabetes self‐management and are integrated into care delivery, we must address issues associated with the use of multiple mHealth devices and the use of aggregate data to support T2DM self‐management. Clinical Relevance: Real‐time patient‐generated health data that are easily accessible and readily available can assist T2DM self‐management and catalyze conversations, leading to better self‐management. Our findings lay an important groundwork for understanding how individuals with T2DM can use multiple mHealth devices simultaneously to support self‐management.